A contextualização no ensino da matemática - Nogueira Neto, Euclides (2019)
Brazil has not achieved good results in our students learning indexes, this fact was proved in 2009, when was performed the Program for International Student Assessment (PISA), in the worldwide scenario Brazil went in 53th in a group of sixtyone countries regards to mathematics. In 2012, in 65 evaluated nations, Brazil was classified in 58th, scored 391 points regards to mathematics, and the most recent result Brazil went 66ª between 70 countries evaluated. With this current result it is clear that we have not achieved referred to the quality of mathematics teaching in our country. This work has as general objective to identify the difficulties found in the pedagogical practices of a group of Primary and Secondary Teachers using a teaching tool of making contextualized mathematical, as well as the knowledge of these teachers about the problem addressed: contextualization. The methodology used in this study is a descriptive research, an analysis of data on current practices or opinions of the mathematics teachers involved in the research, carried out through questionnaires, interviews and observations, taking into account the matter of contextualization of the mathematical contents and the difficulties faced. The results show that teachers who teach in initial grades face less difficulties in contextualizing Mathematics, in arousing their students' interest in the class, when compared to the opinions of teachers who teach in final grades, especially in High School. Throughout this work, the problematic of Mathematics teaching will be widely discussed and suggestions will be given for a more contextualized teaching that will give the student a better learning and a greater satisfaction with his studies